2015
DOI: 10.1587/transinf.2014edp7174
|View full text |Cite
|
Sign up to set email alerts
|

Recommender System Using Implicit Social Information

Abstract: SUMMARYSocial recommendation systems that make use of the user's social information have recently attracted considerable attention. These recommendation approaches partly solve cold-start and data sparsity problems and significantly improve the performance of recommendation systems. The essence of social recommendation methods is to utilize the user's explicit social connections to improve recommendation results. However, this information is not always available in real-world recommender systems. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…As shown in Figure 11, it can be concluded that the recommendation accuracy can achieve its better performance when = 0.4; i.e., the trust relationship and the similarity reach a balance on the Epinions and Tencent datasets, respectively. The regularization constant of user feature in [18][19][20][21][22].…”
Section: Results Of the Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure 11, it can be concluded that the recommendation accuracy can achieve its better performance when = 0.4; i.e., the trust relationship and the similarity reach a balance on the Epinions and Tencent datasets, respectively. The regularization constant of user feature in [18][19][20][21][22].…”
Section: Results Of the Experimentsmentioning
confidence: 99%
“…where denotes the parameter of time attenuation and t ui and t vi denote the times of the item i rated by users u and v, respectively. The improved similarity between user u and user v is described as follows (see (22)):…”
Section: Definition 2 Average Similarity Standard Deviation (Assd)mentioning
confidence: 99%
See 3 more Smart Citations